A metacognitive training program effects on metacognition affect and writing proficiency - Tanael, Judy S. (2006)
The intangible nature of emotion and metacognition and how it affects action, particularly the act of writing and producing written works, was particularized and investigated in this study. A metacognitive training program was designed and afterwards conducted for six weeks to a group of students that served as the experimental group. Two intact classes taking up English 10 at the University of the Philippines Diliman campus participated in the study. The metacognitive training appeared to have a significant effect on the correlations between metacognitive and affective factors by subtracting or adding links or connections among the factors measured. It was recommended that students and more importantly teachers undergo intensive metacognitive training programs.